A study on dose conversion from a material to human body using mesh phantom for retrospective dosimetry. (July 2019) - Kim, Min Chae; Kim, Hyoungtaek; Han, Haegin; Lee, Jungil; Lee, Seung Kyu; Chang, Insu; Kim, Jang-Lyul; Kim, Chan Hyeong
Abstract: In case of a radiation emergency, thermoluminescence (TL) and optically stimulated luminescence (OSL) measurements from materials in a mobile phone have been developed to enable classification of exposed individuals within a short period of time. A reconstructed dose from a mobile phone does not, however, correspond directly to a human body dose. Therefore, several studies were tried to convert a phone dose to a human body dose. Because of the difficulty in obtaining conversion factors experimentally, Monte Carlo simulations have been carried out using human phantoms for various accident situations. In recent years phantoms made of mesh have been developed to solve some problems in traditional voxel phantoms such as limited posture. In the present study, simulations using the GEANT4 computer code were performed to obtain conversion factors using mesh phantoms. The geometry of a mobile phone was designed, reflecting latest structures, and a display glass was selected as a dosimetric material due to its wide detection area with a high radiation sensitivity. Four different positions (chest, hip, thigh, and hand) of a mobile phone on the phantom were considered. In addition, six exposure conditions of anterior-posterior (AP), posterior-anterior (PA), left-lateral (LLAT), right-lateral (RLAT), isotropic (ISO), and rotational (ROT) exposure geometries and three different postures of standing, kneeling, and squatting were selected to reflect actual working situations. Three commonly used radiation sources (Iridium-192, Cesium-137, and Cobalt-60) were applied. Highlights: Simulation was conducted to convert a phone dose to human body dose using the mesh phantoms for various postures. The evaluated doses of a mobile phone were differently affected by body shielding effects. Four different positions (chest, hip, thigh, and hand) of a mobile phone on the phantom were considered.